Análisis financiero de la incidencia del covid-19 en la “Compañía de transporte de carga pesada Transzuriel Cía. Ltda.” periodos 2019-2020. - Ordóñez Gualán, Verónica Alexandra (2023)
The degree work called FINANCIAL ANALYSIS OF THE INCIDENCE OF COVID-19 IN THE ''HEAVY LOAD TRANSPORTATION COMPANY TRANSZURIEL CIA LTDA'', PERIODS 2019-2020, was carried out to comply with the general and specific objectives in order to know the financial-economic situation of the Company. A descriptive investigation is applied including the following methods: scientific, deductive, inductive, analytical, mathematical and statistical; According to the subject of work, it is necessary to consider the decrees and agreements that the Ecuadorian government established during Covid-19, Decree No.1017- Declaration of State of Exception, Decree No.1074 -Declaration of State of Exception in Ecuador, Decree No.1126-Renewal of the State of Exception due to the health emergency and Ministerial Agreement No. 011-2020 of the Ministry of Transport and Public Works, aimed at transport in addition to the use of the safe conduct. In compliance with the first specific objective, the vertical and horizontal analysis was applied, in what corresponds to its assets, most of them are made up of the credit portfolio to customers and other accounts receivable with 62.99% (2019). and 55.83% (2020). Liabilities represent 92.12% (2019) and 94.44% (2020), compared to equity of 7.89% (2019) and 5.56% (2020), deducing that the highest percentage belongs to creditors, while shareholders hold the complement. The income obtained constitutes the largest part for both periods, with $249,664.59 (2019) and a value of $80,642.02 (2020), product of contracts signed as public companies (Vialsur E.P, Municipality of Loja) and in addition to the services of transportation provided to the private company; however, a decrease is reflected between the periods, affecting the profit for 2019 of $2,141.79 and for 2020 it decreases to $579.76, due to the health emergency, which affected the entire business area in its income. According to the second specific objective in the application of indicators, a Current liquidity of 2.84 (2019) and 1.51 (2020) is obtained, which is evident at a glance that the company can cover its short-term obligations, It should be noted that there is a high amount in accounts receivable, which could lead to false liquidity, in the turnover of accounts receivable of 9.57 in (2019) and 3.27 in (2020) it can be deduced that it lacks of credit policies, collection, which is recovered in 37 days (2019) and for 2020 in 110 days to this period the various factors are added during the Covid-19. There is a high degree of indebtedness of assets and equity, which means that it is indebted to third parties. In compliance with the third objective, the financial report was prepared based on the results obtained, presenting recommendations that allow managers and administrators to make the right decisions.